BALL COMPARISON OF THREE METHODS OF CONVERGENCE ORDER SIX UNDER THE SAME SET OF CONDITIONS - Argyros, I. K.; George, S. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2018)
The aim of this paper is to compare the convergence radii of three methods of convergence order six under the same conditions. Moreover, we expand the applicability of these methods using only the first derivative in contrast to earlier works using hypotheses on derivatives up to order seven although these derivatives do not appear in the methods. Numerical examples complete this study.